My Wonderful, Wrong Voice: A Phenomenological Study of Two Trans Individuals’ Experiences of Singing in Swedish Higher Music Educational settings - Hentschel, Linn (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2025)
Global research on the experiences of trans individuals singing within music education is limited and can be considered a blind spot in Scandinavian research. This article investigates two trans individuals’ (female-to-male) experiences of singing in higher music education settings during hormone replacement therapy and poses the following questions: How do the participants experience aspects of the singing body in music education settings—as elements they can or cannot change? What impact do these experiences have on the choices made by the participants regarding singing in music education settings? Between 2014 and 2018, four interviews were conducted with one participant and six with the other. These were then analysed using a phenomenological hermeneutical method of researching lived experience. Results show that experiences of gender and/or the singing voice in music education settings exemplify how biological and social aspects are intertwined and in flux, both related to the body’s facticity and freedom. These intertwinements do not always align with traditional views of how experienced singers should sound or how singing should be organised in music education settings (such as choirs). Consequently, trans singers in Swedish music education settings might experience gender-affirming treatments such as hormone replacement therapy as impossible to “hide”, forcing them to be open about their transition. This could, in a worst-case scenario, be experienced as discriminatory.